Coupled effect of cement hydration and temperature on hydraulic behavior of cemented tailings backfill - Wu, Di; Cai, Si-jing (Journal of Central South University, 2015)
Cemented tailings backfill (CTB) is made by mixing cement, tailings and water together, thus cement hydration and water seepage flow are the two crucial factors affecting the quality of CTB. Cement hydration process can release significant amount of heat to raise the temperature of CTB and in turn increase the rate of cement hydration. Meanwhile, the progress of cement hydration consumes water and produces hydration products to change the pore structures within CTB, which further influences the hydraulic behavior of CTB. In order to understand the hydraulic behavior of CTB, a numerical model was developed by coupling the hydraulic, thermal and hydration equations. This model was then implemented into COMSOL Multiphysics to simulate the evolutions of temperature and water seepage flow within CTB versus curing time. The predicted outcomes were compared with correspondent experimental results, proving the validity and availability of this model. By taking advantage of the validated model, effects of various initial CTB and curing temperatures, cement content, and CTB’s geometric shapes on the hydraulic behavior of CTB were demonstrated numerically. The presented conclusions can contribute to preparing more environmentally friendly CTB structures.